An unexpected complication after removing bladder foreign body: a case report - Gong, Pengfeng; Shen, Jie (Frontiers in Surgery, 2024)
Background: Bladder foreign bodies commonly arise as urgent issues in urology. These foreign bodies are typically extracted through cystoscopy or cystotomy. Generally, these surgical approaches rarely lead to serious complications. Methods: A 34-year-old female presented with a one-year history of frequent urination, urgency, and urodynia. Abdominal CT revealed the presence of an intrauterine device（a medium-sized(20*22mm) circular IUDnear the posterior bladder wall. The object was successfully removed via cystoscopy. Two months later, the patient exhibited food residues in her urine. Enterography demonstrated a large amount of contrast agent had entered the bladder from the small intestine. . We repaired the bladder with catheter for 2 weeks, removed the segment of small intestine with fistula, and anastomosed the intestine canal. Results: Post-operation, urine tests yielded negative results, and the patient resumed a normal diet. Conclusions: Evaluating the location between foreign body and bladder wall, which is based on medical history, CT and cystoscopy examination, is essential for doctors before they remove the foreign body by cystoscopy or laparoscopy. . It is necessary to check for leakage by applying radioopaque fluids under fluoroscopy after removing the foreign body, which migrates from other abdominal organs. If there is damage in bladder or other organs, laparoscopic surgery or open surgery should be performed immediately.